Uric acid‐induced endoplasmic reticulum stress triggers phenotypic change in rat glomerular mesangial cells. Issue 10 (19th September 2013) - Li, Shasha; Zhao, Fei; Cheng, Shaoli; Wang, Xinyang; Hao, Yaning
Abstract Aim The aim of this study was to explore the contribution and the mechanism of uric acid (UA) to phenotypic change in rat glomerular mesangial cells. Methods Rat glomerular mesangial cells (HBZY‐1) were exposed to UA (0.05 mmol/L to 0.4 mmol/L) for 24 h to 48 h. Subsequently, 4‐phenyl butyric acid (4‐PBA) (5 mg/dL) was added and 48 h incubation was performed. HBZY‐1 cells exposed to UA (0.4 mmol/L) were incubated for 48 h. After incubation, the cells were examined under an inverted microscope and transmission electron microscope to observe their morphologies and the expressions of α‐smooth muscle actin (α‐SMA), transforming growth factor‐β1 (TGF‐β1), fibronectin (FN), glucose regulated protein 78 (GRP78), and the protein disulfide isomerase (PDI) proteins and mRNA in the HBZY‐1 cells were measured by Western blot and reversed transcription‐polymerase chain reaction. Results HBZY‐1 cultured in UA showed evident morphological changes under transmission electron microscopy. The soluble UA stimulated the upregulation of the α‐SMA, TGF‐β1 and FN mRNA and proteins in a concentration‐ and time‐dependent manner. UA‐induced endoplasmic reticulum (ER) stress, as evidenced by the upregulation of the mRNA and protein expressions of GRP78 and PDI. However, the upregulation was reverted by 4‐PBA, an inhibitor of ER stress. Conclusions Uric acid induces phenotypic change in HBZY‐1 cells. ER stress plays a central role in UA‐induced phenotypic transformation in vitro. 4‐PBA may be beneficial in attenuating UA‐induced glomerular injury.